Quality of maternal health care in Indonesia - Hanifatur Rosyidah; Korrie De Koning; Hermen Ormel (Journal of Health Technology Assessment in Midwifery, 2019)
Maternal Mortality Ratio (MMR) in Indonesia remains high, 190 per 100,000 live births in 2013. World Bank emphasizes that 60% of maternal death is contributed by poor quality of care. Lack of attitude, competence and compliance of midwives were found in Indonesia, which indicate poor quality of maternal health care. The objective of this study is to analyze factors influencing the quality of maternal health care in Indonesia. The literatures from 2004-2014 were selected and reviewed. The latest framework of 2014 on quality maternal health care by Renfrew et al. was used as a guide. The quality of maternal health care in Indonesia is influenced by lack of midwives’ competence, inadequate supervision and monitoring, lack of drugs and equipment supply, lack of community involvement in health services. In order to address the gaps in quality of maternal health care in Indonesia, six effective interventions are proposed; namely: maternal health audit and feedback, cultural competence, education, educational outreach visit, optimizing the role of lay health workers, group prenatal care and ensure adequate supply of drugs and equipment. The interventions needs to be carried out through a collaborative approach, policy change, pilot study and strengthen activities in implementation level.